PSX-14 The University of Missouri Internship in Bovine Reproductive Management. (7th December 2018) - Knickmeyer, E; Thomas, J; McLean, M; Ciernia, L; Locke, J; Bonacker, R; Decker, J; Smith, M; Patterson, D
Abstract: The reproductive management internship at the University of Missouri is supported by the F.B. Miller Fund and co-sponsored by Select Sires, Inc. The intent of the internship is to provide undergraduate, graduate, and veterinary students with hands-on training in the development and execution of reproductive management strategies for replacement beef heifers and postpartum beef cows. Specific objectives of the F.B. Miller Internship in Bovine Reproductive Management are to: 1) provide students with practical training in development and execution of estrus synchronization and AI programs; and 2) provide extensive hands-on experience in estrus synchronization, estrous detection, semen handling and AI. In 2016, as part of USDA-NIFA grant 2016-68004-24827, training in applied beef genetics was added to the program, including the importance of EPDs, use of genomic prediction, and economic benefits of selection indexes. Over the past 21 years, 236 students have participated in the F.B. Miller Internship and many of them are currently utilizing the training as veterinarians, extension specialists, Animal Science faculty members, allied industry personnel and beef producers. Students in the program participated in hands-on reproductive management procedures on farms and ranches in 12 states. These students have been involved with breeding programs involving over 270, 000 heifers and cows on farms and ranches in these states. Participation fosters a greater appreciation of beef cattle reproductive management, creates links for students with allied industries, and expands career opportunities of the participants following graduation. Students eligible for the internship must have successfully completed a course in reproductive physiology and a course in beef production. Students submit applications and are interviewed by a panel that includes faculty coordinators, representatives of Select Sires Inc., employees, and former interns. Acceptance into the internship is based on scholarship, motivation, work ethic, dependability, personal skills, relevance of the internship to future career goals, and past experience.